2010
DOI: 10.1063/1.3337910
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanoscale confinement on glass transition of polystyrene domains from self-assembly of block copolymers

Abstract: The understanding of size-dependent properties is key to the implementation of nanotechnology. One controversial and unresolved topic is the influence of characteristic size on the glass transition temperature (T(g)) for ultrathin films and other nanoscale geometries. We show that T(g) does depend on size for polystyrene spherical domains with diameters from 20 to 70 nm which are formed from phase separation of diblock copolymers containing a poly(styrene-co-butadiene) soft block and a polystyrene hard block. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 52 publications
13
52
0
Order By: Relevance
“…This means the enthalpic barrier to mixing is negligible, and since the interfacial thickness varies inversely with interfacial energy [35,36], the interphase in these samples is quite extended (as much as a few nm [37e39]). Robertson et al [40] found that in polystyrene block copolymers, a small solubility parameter difference caused very large changes in T g , several tens of K, while a large solubility parameter difference has been found to result in negligible changes in T g [41]. Herein, the presence of the PC within the interfacial region slows down the segmental dynamics of PMMA, significantly increasing its T g .…”
Section: Discussionmentioning
confidence: 99%
“…This means the enthalpic barrier to mixing is negligible, and since the interfacial thickness varies inversely with interfacial energy [35,36], the interphase in these samples is quite extended (as much as a few nm [37e39]). Robertson et al [40] found that in polystyrene block copolymers, a small solubility parameter difference caused very large changes in T g , several tens of K, while a large solubility parameter difference has been found to result in negligible changes in T g [41]. Herein, the presence of the PC within the interfacial region slows down the segmental dynamics of PMMA, significantly increasing its T g .…”
Section: Discussionmentioning
confidence: 99%
“…10 Ultrathin films of polysulfone exhibits no size dependence of T g down to 10 nm, 27 and styrene-isobutylene block copolymer shows weak size dependence. 11 As for the latter, the observed T g variation has been attributed to diffuse interface. Figure 5 shows T g and x(T g ) for the shells with similar thicknesses (17-23 nm) with respect to the degree of crosslink X c .…”
Section: Glass Transition Properties Of Pmma Thin Shells T Sasaki Et Almentioning
confidence: 90%
“…From a practical point of view and for fundamental research on soft matter, it is becoming important to understand the origin of the anomalous dynamics of nano-sized and nano-confined polymers, which differ considerably from the bulk materials. 1 Investigations to clarify the mechanism of such anomalous dynamics have been extensively performed, especially for the glass transition temperature, T g , of ultrathin films, 2-7 and of confined liquids in nanopores, 8,9 spheres 10 and phase separated polymers, 11 but the subject still seems to be a controversial issue. T g depends on various factors including size, status of the interface, geometry and experimental method (sample preparation and observation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors may interact with one another, increasing the complexity of the mechanism that is not yet fully understood. In addition, the size effect on T g has been studied for systems with geometries other than thin film, for example, polymer spheres, 11,12 microphase-separated systems 13 and glass-forming liquids confined in nanopores. 6 In general, the observed T g behaviors for such systems do not necessarily coincide qualitatively with those of thin films, suggesting certain geometry effects on the T g in nanosized materials.…”
Section: Introductionmentioning
confidence: 99%